Analysis of key external and internal load variables in professional female futsal players: a longitudinal study - Oliva-Lozano, J. M.; Muyor, J. M.; Puche Ortuño, D.; Rico-González, M.; Pino-Ortega, J. (Research in Sports Medicine, 2023)
The aims of this study were to identify the key external and internal load variables in professional futsal through principal components analysis (PCA), and analyse the physical performance required by the players in official matches. Data were collected from 14 female players during 10 matches using WIMU PROTM. The PCA selected a total of 22 variables as key indicators of players` load. Specifically, these variables were represented by five principal components. However, a novel finding was that different components were extracted when the analysis was carried out by full match (68.83% of total variance), first half (69.81% of total variance), or second half (65.96% of total variance). Also, this study found that the players decreased their physical performance during the second half. Based on these results, this study may help optimize performance and reduce the injury risk. Performance should not be only analysed considering the full match external/internal load but also specifying by match halves. This is explained by the fact that there were variables that made up the principal components in the first half, but not in the second half or full match. Finally, coaches should adopt training strategies which deal with the decrease in physical performance during the second half.